Heat Adaptation Induced Cross Protection Against Ethanol Stress in Tetragenococcus halophilus: Physiological Characteristics and Proteomic Analysis - Yang, Huan; Yao, Shangjie; Zhang, Min; Wu, Chongde (Frontiers in Microbiology, 2021)
Ethanol is considered as a toxic factor which could injure the membrane structure, disturb the cellular metabolism and even kill the cells. Tetragenococcus halophilus, considered as the cell factory during the manufacture of traditional fermented foods, encountered ethanol stress which would affect the viability and fermentative performance of cells. In order to improve the ethanol tolerance of T. halophilus, strategy based on cross protection was proposed in the current study. The result indicated that cross protection induced by heat preadaptation (45 ℃ for 1.5 h) could significantly improve the stress tolerance (7.24-fold increase in survival) of T. halophilus under ethanol condition (10% ethanol for 2.5 h). Based on this result, a combined analysis of physiological approach and TMT-labeled proteomic technology was employed to investigate the protective mechanism of cross protection in T. halophilus. Physiological analysis showed that the heat preadapted cells exhibited a better surface phenotype, higher membrane integrity, lower membrane permeability and higher amount of unsaturated fatty acids compared to un-adapted cells. Proteomic analysis showed that a total of 163 proteins differentially expressed in response to heat preadaptation. KEGG enrichment analysis showed that energy metabolism, membrane transport, peptidoglycan biosynthesis and genetic information processing were the most abundant metabolic pathways after heat preadaptation. In detail, 3 proteins (GpmA, AtpB and TpiA) involved in energy metabolism and 4 proteins (ManM, OpuC, YidC and HPr) related to membrane transport were up-regulated after heat preadaptation. In all, the results of this study may help understand the protective mechanisms of preadaptation and contribute to improve the stress resistance of T. halophilus during industrial processes.